ENTREPRENEURSHIP IN ROMANIA. COUNTRY REPORT 2013 - SZABÓ, Tünde-Petra; PETE, Ștefan; GYÖRFY , Lehel‐Zoltán; DÉZSI-BENYOVSZKI, Annamária; NAGY, Agnes (2017)
The Global Entrepreneurship Monitor (GEM) is the most important and comprehensiveinternational study of entrepreneurship and the entrepreneurial environment. The GEM studyin 2013 covers 75% of the world’s population and 90% of the world’s GDP. In Romania thestudy is conducted by the Babeş-Bolyai University of Cluj-Napoca, Faculty of Economics andBusiness Administration. A total of 2,021 adults were interviewed in the Adult PopulationSurvey (APS) for this study in 2013. In order to assess the national conditions influencingentrepreneurial activity 36 national experts completed a closed questionnaire on factorsrelated to entrepreneurial environment.The early-stage entrepreneurial activity rate in Romania in 2013 is 10.1% of the adultworking age population. This rate is slightly higher than it was in 2012 (9.22%), it is higherthan the rate registered in Croatia, Hungary and Slovakia and it is similar to the Central-Eastern European efficiency-driven economies’ (CEE) average measured in 2013. Theshare of nascent entrepreneurs decreased from 7.94% in 2012 to 6.2% in 2013. This rate issimilar to Croatia, Hungary, Slovenia, and to the CEE average, but it is lower than theaverage of the world’s efficiency-driven economies. The share of young businessentrepreneurs increased to 4.2% in 2013, from 3.81% in 2012.